2021
DOI: 10.1016/j.ijpam.2020.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lumbar puncture educational video on parental knowledge and self-reported intended practice

Abstract: Background Lumbar puncture (LP) remains an essential diagnostic procedure for neurological and infectious diseases. However, it remains a source of anxiety to patients and families. This research aimed to assess the impact of a newly developed educational simplified video about LP, in the parents’ native language, that is tailored to their social background and beliefs and to assess whether it can facilitate their consent for the procedure. Methods This prospective, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…21 Temsah et al found that video-based counseling similarly improved LPrelated knowledge among parents of children obtaining outpatient clinical care when compared to routine in-person counseling. 22 However, video-based counseling was also associated with increased perception of LP-related risks than routine in-person counseling. 22 This may inadvertently increase LP refusal, although this was not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Temsah et al found that video-based counseling similarly improved LPrelated knowledge among parents of children obtaining outpatient clinical care when compared to routine in-person counseling. 22 However, video-based counseling was also associated with increased perception of LP-related risks than routine in-person counseling. 22 This may inadvertently increase LP refusal, although this was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, video-based counseling was also associated with increased perception of LP-related risks than routine in-person counseling. 22 This may inadvertently increase LP refusal, although this was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 21 , 22 ] Other modalities that could boost parental education are educational videos in parents’ native language, that could be posted on suitable social media platforms. [ 23 ] These educational strategies could be particularly useful for parents without a previous medical background. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…[10,21,22] Other modalities that could boost parental education are educational videos in parents' native language, that could be posted on suitable social media platforms. [23] These educational strategies could be particularly useful for parents without a previous medical background. [24] Several nations have decreased the rates of injury-related deaths in more than 50% of children through educational safety programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation